O3-S2.06 The effect of Trichomonas vaginalis (TV) infection on the vaginal microbiome. (10th July 2011) - Martin, D H; Zozaya-Hinchliffe, M; Lillis, R; Miller, J; Ferris, M
Abstract : Background: Among pregnant women the prevalence of TV infection is highest in women who have intermediate Nugent scores (NS) compared to those with low and high scores reflective of normal and bacterial vaginosis (BV) types of vaginal flora. The goals of this study were to determine if this relationship held true for non pregnant women and to determine if TV infection was associated with changes in the vaginal microbiome. Methods: The study subjects were 394 women enrolled in a cross-sectional study of the aetiology of cervicitis in the New Orleans STD clinic. TV was diagnosed using the InPouch culture method. NS was determined using standard criteria. C trachomatis (CT), N gonorrhoeae (NG), and M genitalium (MG) were diagnosed using NAATs. DNA was extracted from a vaginal swab and stored. Associations between NS and STIs and NS and sexual behaviour were analysed for all 394 women. 454 pyrosequencing analyses were performed on vaginal DNA from 30 TV positive and 30 TV negative samples evenly divided between those with normal, intermediate, and BV flora as determined by NS. Results: 95% of enrolled women were African American and the mean age of the population was 25.6 years. The prevalence of TV (y axis) by 5 NS categories (x axis) is shown in the Abstract O3-S2.06 figure 1 . As opposed to TV, the prevalence rates for CT, GC, and MG were highest among women with NS of 7–10. Also there was no difference in high risk sexual behaviour between those with low and high NS. These data suggested that the striking decrease in TV prevalence observed among women with BV was the result of vaginal environmental factors, not decreased risk for STIs. A heat map based on pyrosequencing data showed that the vaginal flora of 18/30 of the women positive for TV had similar microbiomes which were distinctly different from those of the other 42 women. In the former group, Mycoplasma spp . and Ureaplasma spp . were more abundant than in the latter group while the reverse was true of Megasphaera spp . and Gardnerella spp . Conclusions: Though published research shows that the incidence of TV is highest in women with BV, our data along with those from a previous study in pregnant women clearly establish that TV prevalence is highest in women with intermediate NS. These data in conjunction with our pyrosequencing results suggest that following infection TV modifies the vaginal microbiome by suppressing some of the BV associated organisms and enhancing the abundance of mycoplasmas.